Labor regulation for digital platforms in Chile: Description of Law 21.431 - González Candia, Julio; Hernández Román, Gerardo; Mardones E., María Regina; Von Der Meden, Olivia Zúñiga (Gaceta Laboral, 2024)
This article presents the main aspects of Law No. 21,431 that modifies the Labor Code, regulating the contract of workers of companies of digital service platforms, adding in the aforementioned code chapter X called “Of Labor through digital platforms of services”. The main objectives of the bill were: to create an innovative regulatory framework to adequately protect the people who make use of these platforms for work, which until then were outside the labor legislation; Recognize that the people who use the digital service platforms are workers, whether dependent or independent, with the rights and obligations that this implies and; make the due protection of workers on digital service platforms compatible with job creation and the development of new technologies. The methodological approach used is of a qualitative nature, and its research design presents an exploratory scope - descriptive, non-experimental, transactional, making use of secondary documentation and applying an interpretative analysis. In addition, the article reviews concepts such as the platform economy, globalization, reflexive modernization, risk society, and job insecurity, in order to open a debate and put Law 21,431 in context.